2015
DOI: 10.5455/ajvs.177966
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Foot and Mouth Disease Control Methods among Nomadic Cattle Fulanis in Adamawa State, Nigeria

Abstract: This study analyzed the indigenous foot and mouth disease control methods among nomadic cattle Fulani herders in Adamawa State, Nigeria. Primary data were collected by the use of semi-structured questionnaire administered to randomly selected 363 respondents. Data collected were analyzed using percentages, frequency distribution and regression analysis. Result of the analysis of socioeconomic characteristics of respondents showed that majority were above 40 years of age (87.9%), 94.5% were married and only 16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…Both water and methanol extracts of C. integrifolia were among samples of forty selected medicinal plants found to have potential anti-trypanosome activities by Bizimana et al (2006). The finding from this study is similar to that of Usman et al (2015; that concluded that indigenous control methods were well established and utilized by the respondents. Obtaining information on ethno-veterinary practice is somehow difficult (Nalule et al, 2011).…”
Section: Use Of Indigenous Control Methodssupporting
confidence: 81%
“…Both water and methanol extracts of C. integrifolia were among samples of forty selected medicinal plants found to have potential anti-trypanosome activities by Bizimana et al (2006). The finding from this study is similar to that of Usman et al (2015; that concluded that indigenous control methods were well established and utilized by the respondents. Obtaining information on ethno-veterinary practice is somehow difficult (Nalule et al, 2011).…”
Section: Use Of Indigenous Control Methodssupporting
confidence: 81%
“…Indigenous control methods of cattle parasites are the oldest form of remedies used by cattle herdsmen in Nigeria (Usman, Mani and Mohammed, 2015). These practices remain relevant and vital in the country as a result continued increase in the prices of veterinary drugs, compounded by their prolonged absences from offices of veterinary research institutes in the states and inadequate provision particularly in rural areas (Ojowole, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The list of registered members was obtained from the officials of their association. Based on the list obtained, respondents were randomly selected proportionate to the number of registered members from each of the Local Government Area selected using Taro Yammana's formula as adopted by (Usman et al, 2015). The formula is expressed as; n = N/1+N (e) 2 Where; n = number of respondents N= Population of the study e = error In all, 400 respondents were randomly selected.…”
Section: Sampling Techniquementioning
confidence: 99%